"No there is nothing wrong with your eyes, my letterhead is indeed crooked": An introduction to the study of Black and Brown lesbian educators. Issue 4 (2nd October 2017) - Love, Bettina L.
ABSTRACT: To date, there is a noticeable lack of studies that focus exclusively on the pedagogical practices, teaching experiences, identity, and gender performances of Black and Brown lesbian educators (BBLE). This special issue of the Journal of Lesbian Studies aims to make the hyperinvisibility of BBLE visible and proposes to fill this scholarly gap by exploring this topic from a variety of cultural and disciplinary perspectives.